2022
DOI: 10.3390/mi13081166
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Electrode to Detect Theophylline Based on Copper Oxide Nanoparticles Composited with Graphene Oxide

Abstract: The electrochemical analysis of theophylline (THP) was investigated by fabricating a carbon paste electrode (CPE) modified with graphene oxide (GO) along with copper oxide (CuO) nanoparticles (CuO-GO/CPE). The impact of electro-kinetic parameters such as the heterogeneous rate constant, the scan rate, the accumulation time, the pH, the transfer coefficient, and the number of electrons and protons transferred into the electro-oxidation mechanism of THP has been studied utilizing electrochemical methods such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…As some other authors have reported, a variety of excipients including cellulose, starch, talc, titanium dioxide, sodium lauryl sulfate, lactose, among others, do not interfere with the electrochemical signal of different APIs using different carbon-based working electrodes, even at excipient concentrations ranging from 60 to 100 times higher than the API. [45][46][47][48][49] Likewise, for the electrochemical study of PAR from different authors, no excipient interference was observed. [50][51][52] Since the modified electrodes will be in a solution at 37…”
Section: Interferents Study Electrode Stress Test and Surface Saturationmentioning
confidence: 89%
“…As some other authors have reported, a variety of excipients including cellulose, starch, talc, titanium dioxide, sodium lauryl sulfate, lactose, among others, do not interfere with the electrochemical signal of different APIs using different carbon-based working electrodes, even at excipient concentrations ranging from 60 to 100 times higher than the API. [45][46][47][48][49] Likewise, for the electrochemical study of PAR from different authors, no excipient interference was observed. [50][51][52] Since the modified electrodes will be in a solution at 37…”
Section: Interferents Study Electrode Stress Test and Surface Saturationmentioning
confidence: 89%
“…The unique qualities of hybrid nanoparticles, which can typically not be maintained by a single type of nanoparticle, are imparted by the definitively structured and organized nanocomposites of two or more different nanoparticles . One medication delivery method called composite nanoparticles frequently combines two or more distinct drug carriers, each with a constant dimension in the nanoscale, from the perspective of drug delivery and biological applications. They can be made up of a fusion of two or more inorganic components, organic components, or a combination of both . The final nanocomposite is a blend of a substance with unique synergistic qualities.…”
Section: Introductionmentioning
confidence: 99%
“…The interdigitated electrode is patterned on either of these boards by chemical etching using FeCl 3 , and then the hybrid is spin coated over it. The sensing property can be studied by using the Keithley Source/Measure unit (SMU). …”
Section: Introductionmentioning
confidence: 99%